Simple equation 8

Solve the following equation:

36=-(1+7x)-6(-7-x)

Correct result:

x =  5

Solution:


36=-(1+7x)-6(-7-x)

36=-(1+7•x)-6•(-7-x)

x = 5

Our simple equation calculator calculates it.



We would be pleased if you find an error in the word problem, spelling mistakes, or inaccuracies and send it to us. Thank you!






Showing 0 comments:
avatar




Tips to related online calculators
Do you have a linear equation or system of equations and looking for its solution? Or do you have quadratic equation?

You need to know the following knowledge to solve this word math problem:

Next similar math problems: